Utilization of Palm Oil Liquid Waste for Media Culture and Analysis of Chemical Composition of Microalga Skeletonema costatum - Husna, Hidayatul; syafriadiman, Syafriadiman; Syawal, Henny (Fakultas Perikanan dan Kelautan Universitas Riau, 2023)
This research was conducted in October 2022 at the SUPM Natural Feed Labor/Maritime and Fisheries Polytechnic Pariaman. The purpose of this study was to obtain a suitable dose of palm oil wastewater for culturing Skeletonema costatum microalgae, to analyze the chemical composition of Skeletonema costatum microalgae, to identify the ability of Skeletonema costatum to utilize nitrate and phosphate content in palm oil wastewater, to see the effect of Skeletonema costatum on water quality which has been contaminated with palm oil liquid waste. The method used was an experimental method with a one-factor Completely Randomized Design (CRD) consisting of 6 (six) treatment levels and 3 (three) replications. The treatment given was palm oil wastewater with different concentration treatment levels, namely 0%, 10%, 15%, 20%, 25%, 30% with 3 (three) repetitions so that a total of 18 experimental units, culture carried out for 6 days. The results showed that palm oil wastewater had an effect on the abundance of Skeletonema costatum. The best treatment for Skeletonema costatum culture media was P5 (300 ml/L), cell abundance 329,260 cells/mL, biomass (dry weight) 7.27 g, chlorophyll-a 0.84, nitrate 0.759 mg/L, phosphate 0.301 mg/L, protein 30.70%, fat 0.291% and carbohydrates 21.96%. Meanwhile, a good CO2 is P0 (control), the best dissolved oxygen level is P5 (300 ml/L). Water quality parameters for a temperature of 160C, pH 8.2.